The mediation effect of contraceptive use and women's autonomy on the relationship between intimate partner violence and unintended pregnancy in Ethiopia - Tenaw Yimer Tiruye; Melissa L. Harris; Catherine Chojenta; Elizabeth Holliday; Deborah Loxton (BMC, 2020)
Abstract Background Intimate partner violence (IPV) affects one in every three women globally. Previous studies have revealed that women's experiences of different forms of IPV are significantly associated with a higher rate of unintended pregnancy, reduced uptake of contraception, and reduced ability to make decisions regarding their fertility. The aim of this study was to investigate whether previously observed relationships between IPV and unintended pregnancy in Ethiopia are mediated by contraceptive use and women's autonomy. Methods This study was performed using nationally representative data from the 2016 Ethiopian Demographic and Health Survey (EDHS). A subsample of married women of reproductive age reporting a pregnancy within the 5 years preceding 2016 and who participated in the domestic violence sub-study of the survey were included in analyses. Logistic regression models, together with the product of coefficients method, were used to estimate direct and mediated effects. Results Twenty six percent of participants reported an unintended pregnancy in the 5 years preceding the survey. Sixty-four percent reported having ever experienced IPV (a composite measure of physical, sexual, emotional abuse, and partner controlling behaviour). After adjusting for potential confounding factors, unintended pregnancy was significantly positively associated with reporting sexual IPV, emotional IPV, IPV (a composite measure of physical, sexual, or emotional abuse), and multiple partner controlling behaviour. However, IPV (as a composite of all four forms), physical IPV, and partner control (single act) were not significantly associated with unintended pregnancy. Women's autonomy, but not contraception use, had a significant partial mediation effect in the relationships between some forms of IPV and unintended pregnancy. Women's autonomy mediated about 35, 35, and 43% of the total effect of emotional IPV, IPV (physical, sexual, and/or emotional), and multiple partner control on unintended pregnancy respectively. Conclusion Women's autonomy appears to play a significant role in mediating the effect of IPV on unintended pregnancy in Ethiopia. Maternal health service interventions in Ethiopia could incorporate measures to improve women's decision-making power to reduce the negative reproductive health effects of IPV.